2016
DOI: 10.1093/cid/ciw787
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on Metrics to Assess the Impact of Patient-Level Antimicrobial Stewardship Interventions in Acute-Care Settings

Abstract: Antimicrobial stewardship programs (ASPs) positively impact patient care, but metrics to assess ASP impact are poorly defined. We used a modified Delphi approach to select relevant metrics for assessing patient-level interventions in acute-care settings for the purposes of internal program decision making. An expert panel rated 90 candidate metrics on a 9-point Likert scale for association with 4 criteria: improved antimicrobial prescribing, improved patient care, utility in targeting stewardship efforts, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
79
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 14 publications
0
79
0
3
Order By: Relevance
“…Duration of treatment, or days of therapy, can be used to measure antimicrobial use regardless of changes in antimicrobial doses [55]. Indeed, days of therapy approach was one of six recommended metrics to assess antimicrobial stewardship interventions in acute-care settings according to an expert consensus [60]. Although duration of antimicrobial treatment may not be measured in some settings due to unavailability of patient-level data [53,61], this outcome should be considered in future research focusing on antimicrobial stewardship in care homes.…”
Section: Discussionmentioning
confidence: 99%
“…Duration of treatment, or days of therapy, can be used to measure antimicrobial use regardless of changes in antimicrobial doses [55]. Indeed, days of therapy approach was one of six recommended metrics to assess antimicrobial stewardship interventions in acute-care settings according to an expert consensus [60]. Although duration of antimicrobial treatment may not be measured in some settings due to unavailability of patient-level data [53,61], this outcome should be considered in future research focusing on antimicrobial stewardship in care homes.…”
Section: Discussionmentioning
confidence: 99%
“…A complete discussion of the types of quality measures available for ASPs is outside the scope of this review, but many excellent reviews are available [26,[38][39][40][41]. Measuring antibiotic consumption is the most common type of measure used by ASPs and is integral to identify opportunities for improvement, evaluate the impact of interventions, and participate in interhospital benchmarking [42].…”
Section: Measurement-data Collection and Analysismentioning
confidence: 99%
“…A few studies showed no change or a decrease in Clostridium difficile infection and antibiotic-resistant pathogens, which are important metrics for assessing the patient-level impact of antibiotic stewardship. 4 …”
mentioning
confidence: 99%